EKSEKUSI PUTUSAN PENGADILAN TATA USAHA NEGARA TERHADAP PEJABAT PEMERINTAH DAERAH BERDASARKAN UNDANG-UNDANG NOMOR 9 TAHUN 2004 - ABDUL TAYIB (Universitas Mahasaraswati Mataram, 2021)
The problem examined in this paper is how is the execution of state administrative court decisions against regional government officials based on Law Number 9 of 2004? The approach used is the statutory approach (The Statute Approach) and the conceptual approach (Conceptual Approach). The results of this study indicate that: The process of resolving State Administration disputes which are public disputes involving persons / civil legal entities as plaintiffs and government officials (TUN Officials) as defendants, the legal power of the decision to execute the State Administrative Court which is the executor of judicial power in the environment. The Supreme Court is equivalent to decisions of other judicial bodies. Then the normative changes to the State Administrative Court with Law Number 9 of 2004 concerning Amendments to Law Number 5 of 1986 concerning State Administrative Courts made legal remedies contained in Article 116 such as forced money and/or administrative sanctions and publication of court decisions. be better than using a hierarchical execution model which is considered ineffective in the current era of regional autonomy. Under these circumstances, efforts must be made to provide other alternatives to produce a deterrent effect for government officials, especially local government officials, to submit to the State Administrative Court's decision.